2014
DOI: 10.1179/1743282014y.0000000119
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitations in theDicranum acutifoliumcomplex (Dicranaceae, Bryophyta) using molecular markers

Abstract: Because of their morphological plasticity and broad geographic distribution, the taxonomy of Dicranum is difficult. The circumscription of the different species included in the Dicranum acutifolium complex is poorly understood and taxonomic confusions are frequent. The present study extends earlier internal transcribed spacer (ITS)-based phylogenetic reconstructions of the D. acutifolium complex by analysing five additional chloroplast markers (trnTrps4, trnL-F, psbA-trnH, rps19-rpl2, rpoB) together with ITS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…also Stech and Quandt, 2010 in several species (e.g. Lang et al, 2014b;Tubanova et al, 2010). (Lang et al, 2014a,b), which is supported in the present study, in 403 particular by GMYC (Fig.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…also Stech and Quandt, 2010 in several species (e.g. Lang et al, 2014b;Tubanova et al, 2010). (Lang et al, 2014a,b), which is supported in the present study, in 403 particular by GMYC (Fig.…”
supporting
confidence: 84%
“…Thus, assessing species delimitations in Dicranum is chal-114 lenging both at the morphological and molecular level. Our recent 115 studies on the Dicranum scoparium and D. acutifolium species com-116 plexes (Lang and Stech, 2014;Lang et al, 2014b) as well as on 117 boreal-arctic Dicranum species (Lang et al, 2014a) showed that 118 in several cases conclusive species delimitations could only be 119 obtained from combined analyses of several chloroplast markers 120 and nuclear ribosomal ITS sequences. 121 The present study aims to elucidate species boundaries within 122 Dicranum on a broad geographic scale, including 27 of the 29 123 Dicranum species occurring in Europe (Hedenäs and Bisang,124 2004) plus D. septentrionale Tubanova and Ignatova, a newly 125 recorded species in Scandinavia (Lang et al, 2014b).…”
mentioning
confidence: 98%
See 3 more Smart Citations